First results on the cluster galaxy population from the Subaru Hyper Suprime-Cam survey. II. Faint end color–magnitude diagrams and radial profiles of red and blue galaxies at 0.1 < z < 1.1. (31st October 2017) - Nishizawa, Atsushi J; Oguri, Masamune; Oogi, Taira; More, Surhud; Nishimichi, Takahiro; Nagashima, Masahiro; Lin, Yen-Ting; Mandelbaum, Rachel; Takada, Masahiro; Bahcall, Neta; Coupon, Jean; Huang, Song; et al.
Abstract: We present a statistical study of the redshift evolution of the cluster galaxy population over a wide redshift range from 0.1 to 1.1, using ∼1900 optically-selected CAMIRA clusters from ∼232 deg 2 of the Hyper Suprime-Cam (HSC) Wide S16A data. Our stacking technique with a statistical background subtraction reveals color–magnitude diagrams of red-sequence and blue cluster galaxies down to faint magnitudes of mz  ∼ 24. We find that the linear relation of red-sequence galaxies in the color–magnitude diagram extends down to the faintest magnitudes we explore with a small intrinsic scatter σint ( g  −  r ) < 0.1. The scatter does not evolve significantly with redshift. The stacked color–magnitude diagrams are used to define red and blue galaxies in clusters in order to study their radial number density profiles without resorting to photometric redshifts of individual galaxies. We find that red galaxies are significantly more concentrated toward cluster centers and blue galaxies dominate the outskirts of clusters. We explore the fraction of red galaxies in clusters as a function of redshift, and find that the red fraction decreases with increasing distances from cluster centers. The red fraction exhibits a moderate decrease with increasing redshift. The radial number density profiles of cluster member galaxies are also used to infer the location of the steepest slope in the three-dimensional galaxy density profiles. For a fixed threshold in richness, we find little redshift evolution in this location.